2019
DOI: 10.29271/jcpsp.2019.10.932
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficiency of Laparoscopic Femoral Hernia Repair with Preserved Uterine Round Ligament

Abstract: Objective: To evaluate the efficiency and safety of the transabdominal preperitoneal (TAPP) technique with or without preserved uterine round ligament for the repair of femoral hernias (FHs), on the female patients treated at a single centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Emergency operations due to incarceration strangulation, intestinal obstruction and other complications are associated with expressive morbidity and mortality 7 , 8 , 10 . A multitude of surgical operations have been employed to treat femoral hernias, including open inguinal or femoral access, laparoscopic procedures, use of mesh or plugs and closure of the femoral canal 3 - 5 , 14 , 15 , 17 . In the last decade, laparoscopic access became the preferable access to treat groin hernia for most surgeons 17 , 20 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Emergency operations due to incarceration strangulation, intestinal obstruction and other complications are associated with expressive morbidity and mortality 7 , 8 , 10 . A multitude of surgical operations have been employed to treat femoral hernias, including open inguinal or femoral access, laparoscopic procedures, use of mesh or plugs and closure of the femoral canal 3 - 5 , 14 , 15 , 17 . In the last decade, laparoscopic access became the preferable access to treat groin hernia for most surgeons 17 , 20 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…After reading the title and abstract, 171 studies were excluded, leaving 21 studies, and after reading the full text again, 12 studies were excluded, of which 5 were excluded because the full text was not available, 3 studies did not report the required results, 2 were letters or comments, and 2 did not report sufficient data. In the end, we included 9 studies published between 2015 and 2023 [ 13 – 21 ], including 6 non-randomized controlled studies [ 13 , 15 , 17 19 , 21 ] and 3 randomized controlled studies [ 14 , 16 , 20 ]. The 9 studies included 1104 patients, 578 of whom had the URL preserved and 526 of whom had the URL transected.…”
Section: Resultsmentioning
confidence: 99%
“…Data on age from 7 studies, including 984 patients (528 preservation group and 465 division group) [ 14 – 16 , 18 – 21 ], with high heterogeneity, and were analyzed using a random-effects model (I 2 = 95%, P < 0.00001). There was no significant difference in age between the preservation group and the division group (MD-6.58, 95% CI − 13.41 to 0.24; P = 0.06; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Luk et al 26 found that for female patients undergoing TEP, there was no significant difference in clinical outcomes between those with a transected round ligament and those with a preserved ligament. However, Guo et al 27 found that preserving the round ligament during TAPP can significantly reduce the incidence of postoperative uterine prolapse; however, there was no significant difference in the incidence of postoperative pain, seroma, or recurrence rate. In this study, we transected the round ligament of the uterus into 360 hernias and preserved the remaining 254 sides.…”
Section: Discussionmentioning
confidence: 99%